Peran Kompensasi dan Lingkungan Kerja Sehat dalam Mendorong Loyalitas Kerja Guru - Dwi Agustina Rahmawati; Mudji Kuswinarno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of the study was to determine the role of compensation and healthy work environment in encouraging teacher work loyalty. Case study at RA H. Achmad Ali, Surabaya. The analysis technique used is qualitative descriptive analysis technique, with data collection techniques conducted through interviews and observations. This research method uses a qualitative descriptive approach. The results of the analysis obtained that the compensation obtained by RA H. Achmad Ali teachers is in the form of salaries, allowances, and transportation given once a month. Although with a relatively low nominal compensation does not have a significant impact as a driver of teacher work loyalty, because their commitment is grown from healthy work environment factors that they experience while working. This is evidenced by the running of the learning process in accordance with the rules and objectives, and proven by the length of service of teachers at RA H. Achmad Ali, Surabaya. So it can be concluded that the role of compensation is not significant in encouraging teacher work loyalty, while the role of a healthy work environment is significant and influential in encouraging teacher work loyalty at RA H. Ach Ali, Surabaya.